Vacuolar Phosphate Transporters Contribute to Systemic Phosphate Homeostasis Vital for Reproductive Development in Arabidopsis. Issue 2 (14th December 2018) - Luan, Mingda; Zhao, Fugeng; Han, Xingbao; Sun, Guangfang; Yang, Yang; Liu, Jinlong; Shi, Jisen; Fu, Aigen; Lan, Wenzhi; Luan, Sheng
Abstract : Vacuolar phosphate transporters maintain the systemic Pi homeostasis necessary for reproductive development by contributing to vacuolar Pi sequestration. Abstract: Vacuolar storage of phosphate (Pi) is essential for Pi homeostasis in plants. Recent studies have identified a family of vacuolar Pi transporters, VPTs (PHT5s), responsible for vacuolar sequestration of Pi. We report here that both VPT1 and VPT3 contribute to cytosol-to-vacuole Pi partitioning. Although VPT1 plays a predominant role, VPT3 is particularly important when VPT1 is absent. Our data suggested that the vpt1 vpt3 double mutant was more defective in Pi homeostasis than the vpt1 single mutant, as indicated by Pi accumulation capacity, vacuolar Pi influx, subcellular Pi allocation, and plant adaptability to changing Pi status. The remaining member of the VPT family, VPT2 (PHT5;2), did not appear to contribute to Pi homeostasis in such assays. Particularly interesting is the finding that the vpt1 vpt3 double mutant was impaired in reproductive development with shortened siliques and impaired seed set under sufficient Pi, and this phenotype was not found in the vpt1 vpt2 and vpt2 vpt3 double mutants. Measurements of Pi contents revealed Pi over-accumulation in the floral organs of vpt1 vpt3 as compared with the wild type. Further analysis identified excess Pi in the pistil as inhibitory to pollen tube growth, and thus seed yield, in the mutant plants. Reducing the Pi levels in culture medium or mutation of PHO1, a Pi transport protein responsible for root-shoot transport, restored the seed set of vpt1 vpt3 . Thus, VPTs, through their function in vacuolar Pi sequestration, control the fine-tuning of systemic Pi allocation, which is particularly important for reproductive development.